Effect of Mesh Size on Selectivity of Square Mesh Codends - K.K., Kunjipalu; B., Meenakumari; T., Joseph Mathai; M.R., Boopendranath; R.S., Manoharadoss (Fishery Technology, 2025)
The effect of mesh size on the selective escapement of length class of trawl resources including nine fin fishes and three shell fishes was studied using 20, 25, 30 and 40 mm square mesh codends. Comparatively more juveniles and sub adults were retained in 20 mm square mesh cod ends while 40 mm square mesh permitted escapement of many commercially important groups such as penaeid prawns and squid. 30 mm square mesh cod end has shown compromise size selection properties by providing escapement of most of the juveniles while retaining bulk of economically important species groups. Selectivity parameters and selection curves were determined in respect of twelve species selected for the study.